Productive Fandom - Lamerichs, Nicolle (Amsterdam University Press, 2018)
This book offers a media ethnography of the digital culture, conventions, and urban spaces associated with fandoms, arguing that fandom is an area of productive, creative, and subversive value.
Nederlandse Organisatie voor Wetenschappelijk Onderzoek
English
Keywords: Film theory & criticism; Fandom; inter/transmediality; media ethnography; affect; subcultures